2015
DOI: 10.1038/srep13927
|View full text |Cite
|
Sign up to set email alerts
|

Stacked bilayer phosphorene: strain-induced quantum spin Hall state and optical measurement

Abstract: Bilayer phosphorene attracted considerable interest, giving a potential application in nanoelectronics owing to its natural bandgap and high carrier mobility. However, very little is known regarding the possible usefulness in spintronics as a quantum spin Hall (QSH) state of material characterized by a bulk energy gap and gapless spin-filtered edge states. Here, we report a strain-induced topological phase transition from normal to QSH state in bilayer phosphorene, accompanied by band-inversion that changes n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“…The inverted states are labeled by | ñ p z and | ñ  p x y i . Such band-inversion character may indicate that the topological phase transition from a trivial state to a nontrivial topological state is happened for the dumbbell silicene as σ increases, which is similar to the band-inversion character in bilayer phosphorene [11] and antimonene [52] induced by strain. The Fermi level sitting outside the bulk gap for the dumbbell silicene when σ=-5.0% can be artificially adjusted inside the gap by applying a gate voltage.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The inverted states are labeled by | ñ p z and | ñ  p x y i . Such band-inversion character may indicate that the topological phase transition from a trivial state to a nontrivial topological state is happened for the dumbbell silicene as σ increases, which is similar to the band-inversion character in bilayer phosphorene [11] and antimonene [52] induced by strain. The Fermi level sitting outside the bulk gap for the dumbbell silicene when σ=-5.0% can be artificially adjusted inside the gap by applying a gate voltage.…”
mentioning
confidence: 75%
“…As opposed to three-dimensional (3D) one, its optical, electronic, mechanical and thermal properties are easily adjusted by external strains, defects, electric field, or stacking orders [5][6][7][8], and thus its realistic performance can also be readily improved through current microfabrication technology. 2D materials [9, 10] were first predicted with quantum spin Hall (QSH) effect, and recently more and more 2D materials have been confirmed as 2D topological insulators (TIs) [11][12][13][14], also known as QSH insulator. 2D TIs are novel materials characterized by a bulk energy gap and gapless spin-filtered edge states with the potential application in quantum computation and spintronics [15,16].…”
mentioning
confidence: 99%
“…The most stable ground-state stacking in the bilayers is the AA-configuration. 27,28 The twisted bilayers with Moiré pattern can be considered to be a "mixture" of all possible stacking sequences. Thus the binding energy of the twisted structures is expected to be lower than that of AA-stacking.…”
Section: B Binding Energymentioning
confidence: 99%
“…Thus, understanding the influence of the stacking sequences on the nature of the interlayer interaction among monolayers has been of great fundamental interest. [23][24][25][26][27][28][29] Motivated by this, in this paper we explore the nature of the interlayer coupling and the modulation of the electronic and magnetic properties in twisted bilayers of blue phosphorus (β-P) 30,31 and grey arsenene (β-As), 32,33 both having similar crystal structure and physical properties. Among several possible 2D allotropes predicted for group-V elements, 34 β-P has already been reported experimentally, 35,36 along with a detailed atomistic study of its growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Besides graphene, semiconducting 2D TMDs keep attracting much attention owing to their strong spin‐orbit coupling (inherently much stronger than in graphene) and spin and valley degrees of freedom, offering new opportunities toward valley spintronics . Recent first‐principles studies also reported on the magnetic ordering of phosphorene nanoribbons and the QSH state of bilayer phosphorene, stimulating further experimental and theoretical research.…”
Section: Property Optimizationmentioning
confidence: 99%